Enhancing Family Awareness of Stroke Warning Signs through Supportive Education in a Community Setting - Latipah, Siti; Sofiani, Yani (Babali Nursing Research, 2025)
Introduction: Health education is a key nursing intervention for individuals, groups, or communities to address health issues and promote behavior change for better outcomes. In stroke management, it increases family knowledge of stroke signs and symptoms, helping prevent recurrence. Supportive education further strengthens understanding and awareness of early stroke warning signs, which is crucial to reducing the risk and severity of recurrent strokes. This study examined the relationship between the effectiveness of supportive education and family awareness of warning signs and symptoms in post-stroke patients. Method: A quantitative quasi-experimental pre- and post-design was applied without a control group and a cross-sectional approach. Purposive sampling was used based on inclusion and exclusion criteria. Using G*Power 3.1.9.4 with an effect size of 0.55 and 80% power, 22 participants were recruited. Data were analyzed using inferential statistics, including univariate analysis (frequency distribution) and bivariate analysis (Wilcoxon signed-rank test). The Stroke Recognition Questionnaire (SRQ) showed strong content validity, with a CVI of 0.90 for symptom items and 1.00 for risk factors. Ethical approval was obtained under reference number Un.01/F.10/KP.01.1/KE.SP/05.08.054/2025. Results: Among 22 stroke patients, 40.9% were aged over 65 years, and 72.7% were male. Hypertension was the most common risk factor (86.4%), and 68.2% had a prior stroke. The Wilcoxon test produced a p-value < 0.001, indicating significant improvement in family awareness after supportive education. Conclusion: Effective stroke care requires long-term, comprehensive family involvement with strong self-care skills to support recovery and prevent recurrence.